The Effect of Learning Cycle 5e Learning Model on Students' Motivation and Learning Outcome - Rahmawati, Rahmawati (Journal La Edusci, 2024)
This research aims to determine the influence of the 5E Learning Cycle Learning Model on the Motivation and Learning Outcomes of Class The research population was all grade three consisting of 3 classes with a total of 84 students. The research instrument is a motivation questionnaire and a learning outcomes test in the form of multiple-choice questions. Data was obtained through learning motivation questionnaires and learning outcomes tests. Data analysis techniques are descriptive statistics and inferential statistics with the help of the SPSS 20 application through the One Way Anova test with an error rate of 5% (α = 0.05). The results of the research show that there is an influence of the 5E Learning cycle learning model on learning motivation and learning outcomes of class.